2004
DOI: 10.1080/02699050310001646224
|View full text |Cite
|
Sign up to set email alerts
|

The effects of Donepezil on traumatic brain injury acute rehabilitation outcomes

Abstract: Preliminary evidence suggests that Donepezil administration early in the rehabilitation stay may have advantageous treatment effects. A prospective, randomized, placebo-controlled clinical trial with standard timing, dosage and treatment duration is recommended to further evaluate treatment efficacy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
25
0

Year Published

2007
2007
2021
2021

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 50 publications
(25 citation statements)
references
References 17 publications
0
25
0
Order By: Relevance
“…The critical role that cholinergic systems have in rehabilitation-linked plasticity raises the possibility that agents augmenting cholinergic functioning, such as cholinesterase inhibitors, may also enhance functional recovery in the setting of rehabilitation after cortical damage resulting from stroke or traumatic brain injury. A few small studies have addressed this possibility, although none have been sufficiently powered to draw clear conclusions (24)(25)(26)(27). These findings support the rationale for proceeding with appropriately designed and powered studies to determine whether augmentation of cholinergic function will improve clinical outcomes after cortical injury; cholinesterase inhibitors are clinically approved to enhance function in patients with Alzheimer's disease (28) and well-tolerated in patients with cortical damage (24).…”
Section: Discussionmentioning
confidence: 78%
“…The critical role that cholinergic systems have in rehabilitation-linked plasticity raises the possibility that agents augmenting cholinergic functioning, such as cholinesterase inhibitors, may also enhance functional recovery in the setting of rehabilitation after cortical damage resulting from stroke or traumatic brain injury. A few small studies have addressed this possibility, although none have been sufficiently powered to draw clear conclusions (24)(25)(26)(27). These findings support the rationale for proceeding with appropriately designed and powered studies to determine whether augmentation of cholinergic function will improve clinical outcomes after cortical injury; cholinesterase inhibitors are clinically approved to enhance function in patients with Alzheimer's disease (28) and well-tolerated in patients with cortical damage (24).…”
Section: Discussionmentioning
confidence: 78%
“…However, in a study by Kaye, Townsend, and Ivins (2003), there were no improvements in memory although participants did report improvement in processing speed. In another study, Walker et al (2004) found no significant improvements in cognition as measured on the Functional Independence Measure Score (FIM) between those on donepezil and controls. In addition to memory and processing-speed improvements, donepezil, as well as other AChE inhibitors, have been found to improve attention and have been associated with an overall increased ability to concentrate, improvements in learning and divided attention (Khateb, Ammann, Annoni, & Diserens, 2005;Tenovuo, 2005;.…”
Section: Traumatic Brain Injury (Tbi)mentioning
confidence: 95%
“…Determining how much recovery is occurring spontaneously, and how much is due to stimulation is particularly difficult in the first six months after injury when it is more likely for patients to have dramatic improvements. The FIM+FAM scale has previously been able to show significant levels of improvement after an intervention with 18 treated TBI patients versus untreated controls 167 . If we see a trend towards benefit with stimulation, but without statistical significance, then we would propose a follow-up trial with a greater number of patients and longer experimental period (e.g.…”
Section: Va Author Manuscriptmentioning
confidence: 99%